1997
DOI: 10.1046/j.1365-2958.1997.5971972.x
|View full text |Cite
|
Sign up to set email alerts
|

Oscillin, an extracellular, Ca2+‐binding glycoprotein essential for the gliding motility of cyanobacteria

Abstract: SummaryElectron microscopic studies have demonstrated that various gliding filamentous cyanobacteria have trichome surfaces with a common structural organization. They contain an S-layer attached to the outer membrane and an array of parallel fibrils on top of the S-layer. In all species studied, the helical arrangement of these fibrils corresponds to the sense of rotation of the organism during the gliding movement. We have investigated the surface fibrils of Phormidium uncinatum using electron microscopic, s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
71
1

Year Published

2002
2002
2024
2024

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(74 citation statements)
references
References 22 publications
2
71
1
Order By: Relevance
“…Like most S-layer proteins, AfpA contains no cysteine residues (26). S-layer and RTX proteins such as oscillin (36), SwmA, a cell surface protein required for motility in water (7), and AfpA all contain a combination of predicted calcium-binding motifs and N-glycosylation motifs (Fig. 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…Like most S-layer proteins, AfpA contains no cysteine residues (26). S-layer and RTX proteins such as oscillin (36), SwmA, a cell surface protein required for motility in water (7), and AfpA all contain a combination of predicted calcium-binding motifs and N-glycosylation motifs (Fig. 3 and 4).…”
Section: Discussionmentioning
confidence: 99%
“…The motile cyanobacterium Phormidium unicatum was shown previously to contain fibrillar arrays of a glycoprotein, oscillin, on top of its S-layer. The protein is conserved in motile filamentous cyanobacteria and seems to play a role in gliding motility (13). The S-layer glycoprotein SwmA was shown previously to be required in Synechococcus sp.…”
mentioning
confidence: 99%
“…However, they did observe a tetragonal S-layer external to the outer membrane and, above this, an array of helically arranged surface fibrils, 10 to 12 nm in diameter, with a regular spacing of 14 nm. The fibrils were later shown to consist of a single calcium-binding protein that was given the name oscillin (13). Hoiczyk and Baumeister concluded that the oscillin fibrils served as a screw thread guiding the rotation of the trichome, which was powered by the extrusion of slime from junctional pores that form a ring around the filament on either side of each cell septum (13,14).…”
mentioning
confidence: 99%
“…Hoiczyk and Baumeister concluded that the oscillin fibrils served as a screw thread guiding the rotation of the trichome, which was powered by the extrusion of slime from junctional pores that form a ring around the filament on either side of each cell septum (13,14). They were also able to show that spontaneous, nonmotile mutants of Phormidium uncinatum failed to produce extracellular slime and lacked the S-layer and oscillin fibrils, implying that one, or more, of these components was essential for motility.In a previous study of several motile filamentous cyanobacteria, we demonstrated the presence of a parallel array of 25-to 30-nm diameter fibrils, situated between the peptidoglycan and the OM (3); these fibrils are much wider than those reported by Halfen and Castenholz (11) and Hoiczyck and Baumeister (12,13). The OM was seen to penetrate between the rows of fibrils, and as a consequence the outer surface of the cells appeared corrugated rather than smooth.…”
mentioning
confidence: 99%
See 1 more Smart Citation